Produktivitas Padi sebagai Indikator Modernisasi Pertanian dan Kaitannya dengan Ketahanan Pangan di Jawa Tengah Tahun 2023 - Fuadi, Rohmi Fuadi; Istiqomah (JURNAL AGRICA, 2025)
Rice productivity is an essential indicator of agricultural modernization and a key determinant of regional food security. This study aims to analyze the relationship between rice productivity and the Food Security Index (FSI) in Central Java Province, as well as to identify the role of productivity in strengthening regional food security. The research employs secondary data from all districts and cities, analyzed quantitatively through descriptive statistics, correlation, and linear regression methods. The results reveal a positive relationship between rice productivity and food security, indicating that regions with higher productivity tend to achieve better food security conditions. Although the contribution is relatively limited, the findings confirm that improving productivity as part of agricultural modernization remains an important factor in enhancing regional food security. The study implies that agricultural development policies should emphasize production efficiency, technological adoption, and farmer institutional strengthening to support a sustainable food system.